The spectrum of human immunodeficiency virus-associated cancers in a South African black population: results from a case-control study, 1995-2004. - Stein, L; Urban, M; O'Connell, D; Yu, X; Beral, V; Newton, R; Ruff, P; Donde, B; Hale, M; Patel, M; Sitas, F (2008)
The effect of the evolving HIV epidemic on cancer has been sparsely documented in Africa. We report results on the risk of cancer associated with HIV-1 infection using data from an ongoing study. A case-control analysis was used to estimate the relative risk (odds ratio, OR) of cancer types known to be AIDS defining: Kaposi's sarcoma (n = 333), non-Hodgkin lymphoma (NHL, n = 223) and cancers of the cervix (n = 1,586), and 11 cancer types possibly associated with HIV infection: Hodgkin lymphoma (n = 154), cancers of other anogenital organs (n = 157), squamous cell cancer of the skin (SCC, n = 70), oral cavity and pharynx (n = 319), liver (n = 83), stomach (n = 142), leukemia (n = 323), melanoma (n = 53), sarcomas other than Kaposi's (n = 93), myeloma (n = 189) and lung cancer (n = 363). The comparison group comprised 3,717 subjects with all other cancer types and 682 subjects with vascular disease. ORs were adjusted for age, sex (except cervical cancer), year of diagnosis, education and number of sexual partners. Significantly increased risks associated with HIV-1 infection were found for HIV/AIDS associated Kaposi's sarcoma (OR = 47.1, 95% CI = 31.9-69.8), NHL (OR = 5.9, 95% CI = 4.3-8.1) and cancer of the cervix (OR = 1.6, 95% CI = 1.3-2.0); Hodgkin's disease (OR = 1.6, 95% CI = 1.0-2.7), cancers of anogenital organs other than the cervix (OR = 2.2; 95% CI = 1.4-3.3) and SCC (OR = 2.6, 95% CI = 1.4-4.9) were also significantly increased. No significant associations were found between HIV and any of the other cancers examined. Risks for HIV-related cancers are consistent with previous studies in Africa, and are lower when compared to those observed in developed countries.